Prosecution of Domestic Violence Cases in the United States, 1993-1994 - Rebovich, Donald ([Verlag nicht ermittelbar], 2000)
The purpose of this project was to evaluate the level of domestic violence prosecution throughout the United States and to promote effective prosecution approaches through dissemination of information. The project sought to identify and connect local attorneys' needs for information with the best knowledge available on the most effective prosecution methods. In order to appraise domestic violence prosecution in the United States, the researchers mailed a survey to a nationally-representative sample of prosecutors to assess prosecution strategies in domestic violence cases (Part 1, Prosecutors' Survey Data). Smaller jurisdictions had such a low response rate to the initial survey that a modified follow-up survey (Part 2, Prosecutors' Follow-Up Data) was administered to those jurisdictions. From these surveys, the researchers identified three sites with pioneering specialized domestic violence prosecution programs: Duluth, Minnesota, King County, Washington, and San Francisco, California. In these three sites, the researchers then conducted a case file analysis of a random sample of domestic violence cases (Part 3, Case File Data). A survey of a random sample of female victims was also undertaken in King County and San Francisco (Part 4, Victim Interview Data). In addition, the researchers conducted on-site evaluations of these three specialized programs in which they interviewed staff about the scope of the domestic violence problem, domestic violence support personnel, the impact of the program on the domestic violence problem, and recommendations for the future. The qualitative data collected from these evaluations are provided only in the codebook for this collection. Parts 1 and 2, the Prosecutors' Surveys, contain variables about case management, case screening and charging, pretrial release policies, post-charge diversion, trial, sentencing options, victim support programs, and office and jurisdiction demographics. Questions cover the volume of domestic violence prosecutions, formal protocols for domestic violence prosecution, ways to deal with uncooperative victims, pro-arrest and no-drop policies, protection orders, types of evidence used, and collaboration with other organizations to prosecute domestic violence cases. In addition, Part 1 includes variables on diversion programs, victim noncompliance, substance abuse problems, victim support programs, and plea negotiations. Variables in Part 3, Case File Data, deal with reporting, initial and final charges, injuries sustained, weapons used, evidence available, protection orders issued, victim cooperation, police testimony, disposition, sentence, costs, and restitution for each domestic violence case. Part 4, Victim Interview Data, includes variables concerning victims' employment history, number of children, and substance abuse, opinions about the charges against the defendant, decision-making in the case, and prosecution strategies, and victims' participation in the case, amount of support from and contact with criminal justice agencies, safety concerns, and performance evaluations of various levels of the criminal justice system.